The effect of letrozole and clomiphen citrate in mature follicle count, ovulation and endometrial thickness in unovulated cycle women - Maryati, Sri (Indonesian Journal of Obstetrics and Gynecology, 2009)
Objective: To know the efficacy of letrozole and clomiphene citrate for ovulation induction in anovulation women. Method: During the period of January-October 2007, 44 women who met criteria for an ovulation age 18-35 years old, were done anamnesis, physical examination, USG, and hormonal analysis (FSH, LH, E2, Progesterone and Prolactin). All participants were divided into letrozole and clomiphene citrate group. For the letrozole group received 2,5 mg letrozole daily on 3th until 7th day menstrual cycle. The clomiphene citrate group received 50 mg twice a day, on 3th until 5th day menstrual cycle. On 12th menstrual cycle the ultrasound examination was perfomed to measure number of mature follicle and endometrial thickness. On the 18th day of menstrual cycle, ultrasound was perfomed to evaluate ovulation. Result: There was significant difference between letrozole group and clomiphene citrate group (p=0.04) with the number if follicles in letrozole group is 1.08 (±0.27), in clomiphene citrate group 1.40 (±0.51). There was no significant different in mean of follicle size (p=0.32). Ovulation in both groups was not significantly different (p=0.53), 59% in letrozole group and 68% in clomiphene citrate group. There was significant difference in endometrial thickness, mean of endometrial thickness in letrozole group is 8.77 mm (±2.32 mm) and in clomiphene citrate group 6,66 mm (±2.34 mm) (p